Pengaruh Model Pembelajaran Contextual Teaching and Learning terhadap Motivasi Belajar Pendidikan Agama Kristen dan Budi Pekerti Kelas XI SMK Negeri 2 Balige Tahun Pembelajaran 2024/2025 - Tessa Lonika Hutagalung; Hasudungan Simatupang; Dame Taruli Simamora; Tahdodo Waruwu; Pestaria Naibaho (Sekolah Tinggi Pastoral Kateketik Santo Fransiskus Assisi, 2024)
This study aims to determine the positive and significant influence of the Contextual Teaching and Learning model on the learning motivation of Christian Religious Education and Character Education of class XI SMK Negeri 2 Balige in the 2024/2025 academic year. The method used is a quantitative research method with inferential statistics, because the research conducted is a sample study and the results are applied to the population. The population of this study consisted of 265 students in class XI SMK Negeri 2 Balige who were Protestant Christians and a sample of 53 people was determined using random sampling. The research instrument was a closed questionnaire. The results of the data analysis study obtained: a) Test of influence r count = 0.397> r table = 0.279; b) Significance test t count = 3.090> t table = 2.021; c) Regression equation Ŷ = 35.40  0.53; d) The coefficient of determination test shows that the influence is 15.8%; e) Hypothesis test Fcount = 9.57> Ftable = 3.23 then H0 is rejected and Ha is accepted. The study concluded that there is a positive and significant influence between the Contextual Teaching and Learning learning model on the motivation to learn Christian Religious Education and Character Education of class XI SMK Negeri 2 Balige in the 2024/2025 academic year.